2008
DOI: 10.1007/s11999-007-0071-9
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Isolated Patellofemoral Osteoarthritis

Abstract: Isolated patellofemoral osteoarthritis in the healthy middle-aged population is a challenging problem. Fifty-one knees in 50 patients with isolated patellofemoral osteoarthritis were treated by partial lateral facetectomy, lateral release, and medialization of the tibial tubercle. The minimum followup was 7 months (mean, 20.2 months; range, 7-32 months

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 32 publications
2
46
0
1
Order By: Relevance
“…15 This procedure later became the procedure of choice for treatment in isolated patellofemoral osteoarthritis which showed clinical improvement after the operation in short-term and long-term results even in lateral facetectomy alone [16][17][18] or combined with other procedures such as lateral retinacular release or tibial tubercle osteotomy. 19,20 Our study found decreasing peaks of the patellofemoral contact pressure after the lateral facetectomy, which supported the results of previous studies. Zhang et al stated that lateral facetectomy in non-resurfacing TKR reduced tensions at the lateral retinaculum and decreased the mismatch of the femoral component and lateral facet of the patella.…”
Section: Discussionsupporting
confidence: 91%
“…15 This procedure later became the procedure of choice for treatment in isolated patellofemoral osteoarthritis which showed clinical improvement after the operation in short-term and long-term results even in lateral facetectomy alone [16][17][18] or combined with other procedures such as lateral retinacular release or tibial tubercle osteotomy. 19,20 Our study found decreasing peaks of the patellofemoral contact pressure after the lateral facetectomy, which supported the results of previous studies. Zhang et al stated that lateral facetectomy in non-resurfacing TKR reduced tensions at the lateral retinaculum and decreased the mismatch of the femoral component and lateral facet of the patella.…”
Section: Discussionsupporting
confidence: 91%
“…Operative treatment: Arthroscopy: 2 randomized controlled trials (165 and 168 patients) were included based on indirect evidence (Moseley et al 2002, Kirkley et al 2008)Chondroplasty, resection-arthroplasty, and lateral facetectomy: 1 prospective case series (50 patients) (Becker et al 2008) and 4 retrospective case series (11–63 patients) (Beltran 1987, Yercan et al 2005, Spak and Teitge 2006, Paulos et al 2008)Extensor mechanism alignment and lateral release: 2 prospective case series (35 and 50 patients) (Alemdaroglu et al 2008, Becker et al 2008), 2 retrospective comparative studies (12 and 48 patients) (Weaver et al 1991, Jacquot et al 2004), and 3 retrospective case series (14–50 patients) (Aderinto and Cobb 2002, Kohn et al 2004, Carofino and Fulkerson 2008)Patellectomy: no studies met the inclusion criteriaTotal knee arthroplasty: 2 matched case-control studies (94 and 54 patients) of total knee arthroplasty for isolated patellofemoral osteoarthritis compared with total knee arthroplasty for tri-compartmental osteoarthritis (Laskin and Van Steijn 1999, Meding et al 2007), 1 prospective case series (24 patients) (Parvizi et al 2001), and 3 retrospective case series (25–47 patients) (Mont et al 2002, Dejour et al 2004, Dalury 2005)Patellofemoral arthroplasty: 3 systematic reviews of case series (538–812 patients) (Leadbetter et al 2005, 2006, Becher et al 2008), 5 prospective case series (15–240 patients) (Arnbjornsson and Ryd 1998, Tauro et al 2001, Merchant 2004, Ackroyd and Chir 2005, Ackroyd et al 2007), and 16 retrospective case series (12–65 patients) (Arciero and Toomey 1988, Cartier et al 1990, Argenson et al 1995, Krajca-Radcliffe and Coker 1996, Mertl et al 1997, De Cloedt et al 1999, Fink et al 1999, de Winter et al 2001, Smith et al 2002, Kooijman et al 2003, Board et al 2004, Argenson et al 2005, Cartier et al 2005, Merchant 2005, Sisto and Sarin 2006, Gadeyne et al 2008). …”
Section: Resultsmentioning
confidence: 99%
“…Se incluye la clasificación de Iwano para la presencia de artrosis patelofemoral, ya que las anomalías de alineamiento de la extremidad inferior y otros factores como la displasia troclear, malrotación tibial, dirección/ magnitud de la carga del cuádriceps, etc., pueden jugar un rol en el desarrollo de la alteración, desde condromalasia hasta artrosis en etapas avanzadas (26) . Artrosis en extensión, según Iwano (27) .…”
Section: Musculoesqueléicounclassified